Structure and variation of CRISPR and CRISPR-flanking regions in deleted-direct repeat region Mycobacterium tuberculosis complex strains. (December 2017) - Freidlin, Paul; Nissan, Israel; Luria, Anna; Goldblatt, Drora; Schaffer, Lana; Kaidar-Shwartz, Hasia; Chemtob, Daniel; Dveyrin, Zeev; Head, Steven; Rorman, Efrat
Abstract Background CRISPR and CRISPR-flanking genomic regions are important for molecular epidemiology ofMycobacterium tuberculosis complex (MTBC) strains, and potentially for adaptive immunity to phage and plasmid DNA, and endogenous roles in the bacterium. Genotyping in the Israel National Mycobacterium Reference Center Tel-Aviv of over 1500 MTBC strains from 2008–2013 showed three strains with validated negative 43-spacer spoligotypes, that is, with putatively deleted direct repeat regions (deleted-DR/CRISPR regions). Two isolates of each of three negative spoligotype MTBC (a total of 6 isolates) were subjected to Next Generation Sequencing (NGS). As positive controls, NGS was performed for three intact-DR isolates belonging to T3_Eth, the largest multiple-drug-resistant (MDR)-containing African-origin cluster in Israel. Other controls consisted of NGS reads and complete whole genome sequences from GenBank for 20 intact-DR MTBC and for 1 deleted-DR MTBC strain recognized as CAS by its defining RD deletion. Results NGS reads from negative spoligotype MTBC mapped to reference H37Rv NC_000962.3 suggested that the DR/CRISPR regions were completely deleted except for retention of the middle IS6110 mobile element. Clonally specific deletion of CRISPR-flanking genes also was observed, including deletion of at leastcas2 andcas1 genes. Genomic RD deletions defined lineages corresponding to the major spoligotype families Beijing, EAI, and Haarlem, consistent with 24 loci MIRU-VNTR profiles. Analysis of NGS reads, and analysis of contigs obtained by manual PCR confirmed that all 43 gold standard DR/CRISPR spacers were missing in the deleted-DR genomes. Conclusions Although many negative spoligotype strains are recorded as spoligotype-international-type (SIT) 2669 in the SITVIT international database, this is the first time to our knowledge that it has been shown that negative spoligotype strains are found in at least 4 different 24 loci MIRU-VNTR and RD deletion families. We report for the first time negative spoligotype-associated total loss of CRISPR region spacers and repeats, with accompanying clonally specific loss of flanking genes, including at least CRISPR-associated genescas2 andcas1 . Sincecas1 deletedE.coli shows increased sensitivity to DNA damage and impaired chromosomal segregation, we discussed the possibility of a similar phenotype in the deleted-DR strains and Beijing family strains as both lack thecas1 gene.